MAKNA BUDAYA ETIKA TABEA PADA ETNIK MUNA DI KELURAHAN NAPABALANO KECAMATAN NAPALANO KABUPATEN MUNA - Dian Kristina Sanusi; Ferdinand Kerebungu; Veronike E.T. Salem (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
The problem in this research is how the cultural meaning of tabea ethics in ethnic Muna in Napabalano Village, Napabalano District, Muna Regency. This study aims to examine the cultural meaning of tabea ethics in Muna ethnic groups in Napabalano Village, Napabalano District, Muna Regency. This research is a qualitative descriptive study through direct interviews with religious leaders and traditional figures in the Napabalano Village. The results of this study indicate that the meaning of (1) the Tabea tradition is the customary language of politeness / behavior which means excuse me, namely the more subtle greeting words that are generally spoken when passing in front of people, especially those we respect, friends, friends, parents, or anyone we respect. (2) The word tabea is followed by a downward movement of the right hand towards the ground or ground, the meaning of the behavior of such muna area people is that the word tabea is a symbol of the effort to appreciate and respect anyone in front of us, we should not do what we want. (3) The cultural meaning of Tabea on ethnic Muna in Napabalano Village, Napabalano District, Muna Regency, namely a) Cultural Meaning, b) Social Meaning, c) Education Meaning, d) Family Meaning.